High-performance nonfullerene polymer solar cells with open-circuit voltage over 1 V and energy loss as low as 0.54 eV. (October 2017) - Fan, Qunping; Xu, Zhuo; Guo, Xia; Meng, Xiangyi; Li, Wanbin; Su, Wenyan; Ou, Xuemei; Ma, Wei; Zhang, Maojie; Li, Yongfang
Abstract: In this work, we developed high efficiency nonfullerene PSCs based on a wide bandgap polymer donor PBPD-Th with a structure of meta -alkoxyphenyl benzodithiophene- alt -thienyl benzodithiophene-4, 8-dione and a low bandgap small molecule acceptor ITIC. The PBPD-Th shows a strong absorption in the short wavelength of 300–650 nm with a bandgap of 1.91 eV, which is complementary with that of ITIC (1.55 eV). Moreover, PBPD-Th possesses a deep HOMO level of −5.42 eV, which is beneficial to obtain high open-circuit voltage ( V oc ) in PSCs. As a result, the optimal PSCs based on PBPD-Th: ITIC showed a power conversion efficiency (PCE) of 10.8% with a V oc of up to 1.01 V, a high short-circuit current density ( J sc ) of 18.3 mA cm −2 and a fill factor (FF) of 59%, under the illumination of AM 1.5 G, 100 mW cm −2 . Notably, the energy loss ( E loss ) of the optimal PSCs is 0.54 eV, which is smaller than the empirically low threshold of 0.6 eV. The PCE of 10.8% is one of the highest values reported in the literatures for the PSCs with V oc over 1.0 V. Graphical abstract: Highlights: Efficient nonfullerene PSC based on PBPD-Th: ITIC was developed. The PSC showed a high PCE of 10.8% with a V oc of up to 1.01 V −2 . The PSC has a smaller E loss of 0.54 eV than the empirically low threshold of 0.6 eV.